Definition, Assessment of the Phonological Skills and Their Correlations with the Reading Disability (Dyslexia) - Daniutė , Simona; Staliūnienė , Ingrida (Special Education, 2022)
The article presents a theoretical analysis of the definition and structure of phonological skills: the concept of phonological skills as well as groups of them and correlations with the reading disability (dyslexia) are revealed. Also, the present paper focuses on a comprehensive discussion on characteristics of assessment of phonological skills at both international and national scales.    To reveal the theoretical concept of phonological skills, an analysis of scientific papers published by Lithuanian and foreign authors have been carried out. The conducted analysis of the concept allows declaring that phonological skills encompass phonological awareness, short-term memory and rapid naming. These are perhaps the most frequently analysed phonological processes related to reading and (or) writing in foreign countries. Extensive research conducted in various foreign languages allowed demonstrating obvious correlations between phonological skills and reading disability (dyslexia). It was found out that individuals with dyslexia had insufficient skills in this field. Nevertheless, results of the surveyed long-term investigations demonstrate that two indicators predict reading attainments in pre-school and pre-primary age best: phonological awareness and rapid naming. Similar research works dealing with correlations between phonological skills and reading in the Lithuanian language are quite rare. Therefore, before presenting a firm conclusion based on scientific evidence on the question under investigation, it is necessary to accumulate more empirical data. Moreover, the demand for national research on phonological skills of children with linguistic and speech impairments is obvious.
Keywords: -